ADOLESCENCE UNDER PRESSURE: RELIGIOUS TRAUMA AND IDENTITY IN DILL’S NARRATIVE - Sahruman (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2025)
This study explores the impact of religious extremism on youth identity formation in Jeff Zentner’s novel The Serpent King, focusing on the character Dill who endures psychological conflict due to doctrinal imposition. The aim is to analyse how Dill’s identity evolves in response to trauma and how subcultural elements, particularly music and peer influence, shape his self-reconstruction. Using a qualitative literary approach rooted in sociocultural literary criticism, the study applies thematic analysis on Dill’s narrative progression, drawing from psychological theory (Erikson, Marcia) and sociological perspectives on subculture and trauma (Granqvist & Hagekull, Weinstein). This approach highlights the interplay between religious ideology, youth agency, and cultural resistance. Results indicate that Dill’s religious trauma, coupled with musical subculture and peer relationships, catalyses a resistance identity characterized by self-authorship and resilience. Literature provides a unique framework for understanding such transformation. This study affirms the significance of literature as a medium to examine adolescent identity under ideological pressure, offering insight into resistance, trauma recovery, and the power of interpersonal connection